Determinants of household debt in emerging Asean countries / Nurrain Syahirah Ismail - Ismail, Nurrain Syahirah (Faculty of Business and Management, 2020)
The aim of this study is to investigate the relationship between the household consumption, inflation rate and unemployment rate with the household debt in Asean countries. This study has been adapted from the previous study by Kusairi, Muhamad, Musdholifah, & Chang (2019) and Yahaya & Sarwe (2019). The selected country of four Asean countries are Malaysia, Indonesia, Thailand and Vietnam. The countries are being selected because the household debt in these countries are increasing every year. Therefore, it is critical to analyse the determinants of household debt in these 4 countries because these countries are having the potential to become an emerging market in Asean region. The data is analysed on yearly basis for 19 years, starting from year 2000 until 2018. Data are collected from World Bank Data, CEIC Data and International Monetary Fund Data. This study used Economic Views (E-views) as a tool to analyse the data by employing Panel Regression Random Effect Model. The result shows that all the variables, household consumption, inflation rate and unemployment rate have negative significant relationship with the household debt. The result of study similar with the past study which is using the same independent variables which are household consumption Kittiphongphat (2018), inflation rate (Kusairi et al., 2019; Mutezo, 2014) and unemployment rate (Meng, Hoang, & Siriwardana, 2013; Yahaya & Sarwe, 2019). Therefore, the policymakers, industry, and the banking sector play an important roles to ensure that household debt does not continue to rise every year for economic stability and long-term debt sustainability.